Mebendazole treatment in ascariasis re-infection of two-year-old boy in rural Ambon: a case report and literature review - Thiono, Marischa Tita; Sutjonong, Tioky; Polanunu, Masayu Ramadhani; Husada, Dominicus (Institute of Topical Disease Universitas Airlangga, 2024)
Ascariasis is currently a health problem in developing countries, especially in rural areas. Successful control of ascariasis is highly dependent on therapeutic interventions, environmental, and individual hygiene practices. Ascariasis is generally asymptomatic but can cause severe problems if treated improperly. Treatment is available, but reinfection may occur. This case aims to emphasize the usage of mebendazole treatment in ascariasis reinfection. A two-year-old boy came to the hospital with mucus diarrhea and worms in the stool. Two months ago, he had the same symptoms and experienced improvement after taking pyrantel pamoate at the previous hospital. The patient was diagnosed with acute diarrhea with mild to moderate dehydration, re-infection ascariasis, and malnutrition. Mebendazole 100 mg was administered twice daily for 3 days. Treatment with mebendazole was repeated twice with an interval of one month after the previous therapy due to the presence of Ascaris lumbricoides eggs in fecal examination. Fecal examination in the third month revealed the absence of Ascaris lumbricoides egg. Mebendazole can be used as therapy for ascariasis reinfections. However, repeated therapy is required in some cases. By integrating repeated therapy with comprehensive control measures, including health education and improved sanitation infrastructure, sustainable progress in combating ascariasis can be achieved.